Studying on the Soda and Dioxane Lignin of Bagasse using Derivatization Followed by Reductive Cleavage (DFRC) - vida haji Aghaei; Seeyed Ahmad Mirshokraie; Tayyebe partovi (تحقیقات علوم چوب و کاغذ ایران, 2014)
In this study, the structure of Soda (soluble fraction in ethanol) and Dioxane lignins of bagasse were studied by using derivatization followed by reductive cleavage (DFRC) method and some techniques including gel permeation chromatography, gas chromatography-mass spectrometry and 13C-nuclear magnetic resonance spectroscopy and the results were compared. These comparative results show that the main monomeric compounds are obtained from the cleavage of β-O-4 bonds of lignins. The components obtained from Dioxane lignin and Soda lignin are guaiacyl, syringyl and p-hydroxyphenyl structures with different proportions. However, some differences have been observed in both lignins, including a variety of structural units in Dioxane lignin is greater than Soda lignin. In other words, soda lignin degradation and the structural components has become closer together and are more uniform structures. The average molecular weight of Dioxane lignin, is greater than Soda lignin, which is due to Soda lignin wide chemical degradation during industrial pulping processes and therefore it has less dense structure. These observations indicate that a mild method for lignin separation from a lignocellulosic material caused less damage and changes in lignin structure. Therefore, in structural studies, Dioxane lignin can actually be used as an appropriate representative of the lignin.